Chickpea (Cicer arietinum L.) growth, nodulation, and yield as affected by varieties, Mesorhizobium strains, and NPSB fertilizer in Southern Ethiopia - Nahusenay, Gashaw; Wolde, Girma; Tena, Wondwosen; Tamiru, Tatek (Frontiers in Plant Science, 2024)
A significant legume crop in Ethiopia, chickpeas (Cicer arietinum L.) have several advantages, including high nutritional value and the capacity to improve soils deficient in nitrogen through biological nitrogen fixation using several endosymbiotic Mesorhizobium spp. strains. However, the host variety, the soil’s capacity to hold nutrients, and the endosymbiont’s innate physiological traits all affect how efficient the strains are. The primary obstacles to its cultivation in the research area are inadequate agronomic methods and low soil fertility [low nitrogen (N), low soil organic matter (OM), low accessible phosphorous (P), sulfur (S), and boron (B)], which results in ineffective nodulation. To evaluate the effects of NPSB fertilization and inoculation, a field experiment was carried out in Buchach Kebele’s Cheha area during the primary cropping season of 2021/22. The trial included two chickpea kinds (Local and Arerti), two NPSB levels (zero and 121 kg NPSB ha-1), and four levels of Mesorhizobium strains (CP-M41, CP-EAL 029, CP-M20b, and un-inoculated control). A randomized complete block design (RCBD) was used to organize the treatments in a factorial form with three replications. In comparison to the single application and the control, the interaction impact of strains, NPSB fertilizer, and variety greatly increased nodulation parameters, growth parameters, yield, and yield components. The Arerti variety combined with the CP-M41 Mesorhizobium strain and NPSB fertilizer had the maximum grain production (3177.16 kg ha-1). It yielded 15.96%, 24.06%, and 37.93% more than the Arerti with CP-M41 strain, Arerti with NPSB, and the control treatments, respectively. The partial budget analysis of the study treatments showed that the Arerti variety with the combined application of 121 kg NPSB ha-1 and Mesorhizobium strain CP-M41 inoculation produced the highest net return (102,092.6 ETB ha-1) with an acceptable marginal rate of return (618%). It has been found that the CP-M41 strain and the Arerti variety, when combined with 121 kg NPSB ha-1 application, is a suitable treatment combination to achieve increased chickpea crop yield and profit in the studied area. However, the results need further validation in the farmer’s field before recommending to farmers.